Curvilinear relationship between life's crucial 9 and metabolic syndrome in U.S. adults: a cross-sectional study - Wang, Bo; Jiang, Chunqi; Yu, Pingping; Nie, Zhen; Wang, Ning; Zhang, Xin (Frontiers in Endocrinology, 2025)
BackgroundMetabolic Syndrome (MetS) is closely linked to cardiovascular disease. However, no studies have examined the relationship between Life’s Crucial 9 (LC9) and MetS. Our goal is to investigate the potential association between LC9 and MetS.MethodsWe employed a weighted multivariate logistic regression model to evaluate the relationship between LC9, health behavior score, health factors score, and MetS. To assess the robustness of this association, we conducted sensitivity analyses. Furthermore, we utilized smooth curve fitting to investigate the potential curvilinear relationships between LC9, health behavior score, health factors score, and MetS. To pinpoint inflection points, we integrated recursive partitioning algorithms with a two-stage linear regression model. Additionally, we performed stratified analyses to explore heterogeneity across different population subgroups.ResultsOur study included a total of 28,555 participants. In the regression model that accounted for all covariates, the OR for LC9 and MetS was 0.941 (0.939, 0.944), indicating a significant negative correlation between the two. Smooth curve analysis confirmed a curvilinear relationship between LC9 and MetS, with an inflection point at 70.56. The negative correlation was evident both before and after the inflection point, with a more pronounced effect after the inflection point. Subgroup analyses of Health behavior score and Health factors score, as well as stratified analyses by age, sex, and BMI, showed that all groups exhibited curvilinear relationships consistent with the overall pattern.ConclusionThe curvilinear relationship between LC9 scores and metabolic syndrome indicates that higher LC9 scores act as a protective factor against MetS.